1999
DOI: 10.1086/302624
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a First Locus for Autosomal Dominant Myxomatous Mitral-Valve Prolapse to Chromosome 16p11.2-p12.1

Abstract: Myxomatous mitral-valve prolapse (MMVP), also called Barlow disease, is a common cardiac abnormality and affects up to 5% of the population. It is characterized by an excess of tissue that leads to billowing of the mitral leaflets, sometimes complicated by prolapse. Typical histological findings include myxomatous degeneration and degradation of collagen and elastin. Previous reports have proposed an autosomal dominant inheritance of the trait, with age- and sex-dependent expression. By systematic echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
1
11

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 31 publications
2
100
1
11
Order By: Relevance
“…17) Identification of the locus for autosomal dominant myxomatous MVP to chromosome 16p11.2 -p12.1 was reported. 18) In addition, Xlinked inheritance has been reported in a special form of familial MVP, called myxomatous valvular dystrophy, which has been mapped to Xq28 in a large French pedigree. 19) Low blood pressure and autonomic dysfunction may be regarded as a phenotypic feature of MVP.…”
Section: Discussionmentioning
confidence: 99%
“…17) Identification of the locus for autosomal dominant myxomatous MVP to chromosome 16p11.2 -p12.1 was reported. 18) In addition, Xlinked inheritance has been reported in a special form of familial MVP, called myxomatous valvular dystrophy, which has been mapped to Xq28 in a large French pedigree. 19) Low blood pressure and autonomic dysfunction may be regarded as a phenotypic feature of MVP.…”
Section: Discussionmentioning
confidence: 99%
“…19 Through chromosomal mapping, it has been shown that myxomatous MVP has a genetic heterogeneity which implies mutations located on chromosomes 16, 11 and 13. [20][21][22] Autosomal dominant and X-linked forms have also been cited. 19 Mutations of the fibrillin-1 (FBN1) gene which encodes the fibrillin-1 protein and mutations of the transforming growth factor β (TGF-β) receptor 2 gene are responsible for the occurrence of Marfan's syndrome, as well as MVP.…”
Section: Genetic Causesmentioning
confidence: 99%
“…The exact cause of primary MVP is not completely understood but the contribution of genetic factors is evident. In some family studies, MVP has been linked to chromosomes 16p11.2-p12.1 [3], 11p15.4 [4] and 13q31.3-q32.1 [5]. Others have shown that polymorphisms in several genes are associated with an increased risk of MVP [6][7][8].…”
Section: Introductionmentioning
confidence: 99%